Gender Equity: Employment and Performance - Chiam , Chooi Chea (Springer, 2019)
Gender performativity refers to the productivity of labor based on worker gender. Performativity affects employability and can be categorized into various aspects for study based on age group, gender, job type, and other factors. Gender performativity can indirectly refer to ability and opportunities based on performance. Gender inequality issues have been on the map as a global concern raised in international talks, in forums, and by delegates around the world. The question of equality treatment between genders has become more evident over recent years because of modernization and the era of globalization (Cailin and Leanne 2015). The significant role and contribution of women cannot be ignored, because they do significantly increase the wealth and assist the growth of a household, a firm, and even a country. As a group, women work as much as men, if not more. When both paid and unpaid work such as household chores and caring for children are taken into account, women work... (Abstract by author)